Complex Grant-Contracting and Social Equity: Barriers to Municipal Access in Federal Block Grant Programs. Issue 2 (2nd April 2016) - Collins, Brian K.; Andrew, Simon A.; Khunwishit, Somporn
ABSTRACT: Intergovernmental granting involves complex vertical and horizontal contracting problems. The implementation of some federal social equity programs is a function, in part, of the ability of local governments to contract out. Municipalities with less administrative capacity or in high-contracting-cost environments face barriers to funding. We theorize that in some cases these problems affect equitable access to federal funding and apply this framework to the state-administered nonentitlement Community Development Block Grant (NE-CDBG) program. Utilizing a zero-inflated negative binomial regression, we examine 250 small municipal governments to test the relationship between number of NE-CDBGs grants awarded in 2000–2003 and obstacles to contracting out. Our findings suggest that needs-based access to federal funds is distorted when small cities face obstacles to contracting out as a local managerial strategy. Competitive grant processes and the council-manager form of government also influence grant access, but low- to moderate-income populations do not track the number of grants in an expected direction. Our findings highlight concerns about the ability of small municipalities to access intergovernmental grant programs.